Brief Report: IL-1β Levels Are Associated With Chronic Multisite Pain in People Living With HIV. (1st August 2017) - Merlin, Jessica S.; Westfall, Andrew O.; Heath, Sonya L.; Goodin, Burel R.; Stewart, Jesse C.; Sorge, Robert E.; Younger, Jarred
Abstract : Background: The pathophysiology of chronic pain experienced by people living with HIV (PLWH) in the current antiretroviral treatment era is poorly understood. We sought to investigate the relationship between inflammation and chronic pain in PLWH. We hypothesized that, among PLWH who have undetectable HIV viral loads, those with chronic multisite pain (CMP) would have higher levels of circulating pain-related inflammatory markers than those without chronic pain. Setting: This study was conducted at the University of Alabama at Birmingham's Center for AIDS Research Network of Integrated Clinical System site. Methods: We compared inflammatory markers in 70 PLWH with CMP and 70 PLWH without chronic pain. Custom multiplex human inflammatory assays were completed on banked plasma specimens to measure cytokines commonly associated with chronic inflammatory pain: interleukin 1β (IL-1β), eotaxin, IL-15, IL-6, tumor necrosis factor α, and leptin. Logistic regression models were built using group status (CMP vs no pain) as the outcome variable, with each cytokine as independent variables and age, sex, substance use, and prescribed opioid medications as covariates. Results: Participants were mostly men (71%); 53% were 50 years or older. The most common sites of pain were low back (86%), hands/feet (81%), and knee (66%). Median CD4 + T-cell count was 676 cells per milliliter. IL-1β was significantly higher in the CMP group than in the individuals without chronic pain (odds ratio: 1.35, 95% confidence interval: 1.01 to 1.82, P < 0.05). Eotaxin, IL-15, IL-6, tumor necrosis factor α, and leptin were not significantly different between groups. Conclusions: We found that PLWH who also have CMP have significantly higher levels of IL-1β than PLWH who do not have any pain. Future work on the role of IL-1β on chronic pain pathogenesis in this population may inform novel approaches to chronic pain management.